2007
DOI: 10.1080/14616730701349721
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment, complex trauma symptoms, and unresolved attachment in an at-risk sample of adolescent mothers

Abstract: Associations between unresolved attachment, abuse history, and a wide range of trauma-related symptomatology were examined in an at-risk sample (N = 62). Fifty percent reported severe childhood physical and/or sexual abuse. An independent trauma interview elicited more reports of childhood sexual abuse than the Adult Attachment Interview (AAI); conversely, the AAI elicited more reports of physical abuse. Childhood physical abuse, sexual abuse, and general maltreatment were associated with unresolved status. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
5
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 59 publications
7
115
5
5
Order By: Relevance
“…In the United States, nearly 30% of individuals who seek psychological services are survivors of childhood abuse (Dimitrova et al, 2009). Survivors who have experienced childhood sexual trauma, or any unwanted sexual act prior to the age of 18, are more likely to endorse a myriad of mental health symptomology than are individuals who do not have a history of childhood sexual trauma (Bailey et al, 2007). This symptomology can be consistent with psychological disorders such as PTSD, depression and Bipolar Disorder (Smith et al, 2011).…”
Section: Appendix a Statement Of The Problemmentioning
confidence: 78%
See 3 more Smart Citations
“…In the United States, nearly 30% of individuals who seek psychological services are survivors of childhood abuse (Dimitrova et al, 2009). Survivors who have experienced childhood sexual trauma, or any unwanted sexual act prior to the age of 18, are more likely to endorse a myriad of mental health symptomology than are individuals who do not have a history of childhood sexual trauma (Bailey et al, 2007). This symptomology can be consistent with psychological disorders such as PTSD, depression and Bipolar Disorder (Smith et al, 2011).…”
Section: Appendix a Statement Of The Problemmentioning
confidence: 78%
“…This is particularly true regarding the relationship between childhood maltreatment and interpersonal functioning (Bailey, Moran & Pederson, 2007). In an article assessing 62 women who became mothers during adolescence over a two-year period, results indicated that individuals who experienced sexual trauma during childhood also experienced emotional abuse or additional ATTACHMENT, SELF-ESTEEM AND SUBJECTIVE WELL-BEING 55 traumatic experiences.…”
Section: Childhood Sexual Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…maltreatment, family violence) consistently across numerous studies (Cloitre, Garvert, Brewin, Bryant, & Maercker, 2013; Cloitre, Garvert, Weiss, Carlson, & Bryant, 2014; Dorahy et al, 2014; Knefel et al, 2015; Knefel & Lueger-Schuster, 2013; Wolf et al, 2015). CPTSD as defined by DESNOS is theorized to represent the results of developmental adaptations to exposure to interpersonal trauma in developmentally sensitive periods, including altered emotion processing (Langevin, Hebert, & Cossette, 2015; Shields & Cicchetti, 1998), dissociative shifts in self-awareness and consciousness (Bailey, Moran, & Pederson, 2007; Lyons-Ruth, Dutra, Schuder, & Bianchi, 2006), and disruption of secure attachment working models (Madigan, Vaillancourt, McKibbon, & Benoit, 2012; Stronach et al, 2011). However, whether there is a specific linkage between exposure to potentially traumatic events in childhood and each of the proposed core features of CPTSD as defined by DESNOS has not been systematically investigated.…”
mentioning
confidence: 99%